2015
DOI: 10.4103/0973-6247.154255
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of human T-cell lymphotropic virus type-I in blood donors of Northeastern Iran, Sabzevar

Abstract: Background and Objectives:Human T-cell lymphotropic virus type-I (HTLV-I) infection is considered as a public health challenge in endemic areas. The virus is associated with severe diseases, such as adult T-cell leukemia/lymphoma, and HTLV-I-associated myelopathy/tropical spastic paraparesis. One of the major routes of the HTLV-I transmission includes blood transfusion. Sabzevar is located in the endemic region of HTLV-I infection. The aim of the present study was to determine the seroprevalence of HTLV-I infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Similarly, Emadi et al reported an HTLV-1 prevalence in 4 per 100,000 among 263,465 blood donors aged between 18 and 25 years old, while 66 per 100,000 donors of 46 to 65 years old [51]. Conversely, some studies with considerable sample sizes (from 407 to 35,067 individuals) reported no significant relationship between participants' age and the infection rate [23,36,47,54]. An age-and sex-matched case-control study to assess the HTLV-1 risk factors among "firsttime" Iranian blood donors was performed during the period 2011-2012 [65].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, Emadi et al reported an HTLV-1 prevalence in 4 per 100,000 among 263,465 blood donors aged between 18 and 25 years old, while 66 per 100,000 donors of 46 to 65 years old [51]. Conversely, some studies with considerable sample sizes (from 407 to 35,067 individuals) reported no significant relationship between participants' age and the infection rate [23,36,47,54]. An age-and sex-matched case-control study to assess the HTLV-1 risk factors among "firsttime" Iranian blood donors was performed during the period 2011-2012 [65].…”
Section: Resultsmentioning
confidence: 97%
“…These tests were performed among first-time and regular blood donors, and as a result, many surveys revealed a gradual decrease in HTLV-1 prevalence among Iranian blood donors from 0.13% in 2009 to 0.03% in 2018 (Table 1) [31,32,63]. A declining trend in the infection rate among blood donors was documented in Razavi Khorasan [41,42,45,47] as well as other provinces of Iran [48,51]. However, over time, no change was observed in the HTLV-1 infection rate among the general population of Razavi Khorasan province [21,26,30].…”
Section: Resultsmentioning
confidence: 99%
“…The two clinical conditions are now categorized as severe human diseases of public health importance because of their associated severe immunosuppression and resistance to chemotherapy (Jamilii et al, 2015), and until now there is no known cure or protective vaccine available. In an effort to contain the situation, the Global Virus Network in 2014, launched a taskforce to promote basic research, develop new methods of prevention and treatment modalities including new public health preventive measures.…”
Section: Humanmentioning
confidence: 99%
“…In northeastern Iran, 0.14% of blood donors were found to be seropositive for HTLV-1 [30]. Surveys in southern India and Indonesia have identified some HTLV-1-positive cases; in the Seychelles in the Indian Ocean, HTLV-1 is highly endemic (> 15%).…”
Section: Prevalence Of Infection - Htlv-1mentioning
confidence: 99%